2019
DOI: 10.4046/trd.2018.0044
|View full text |Cite
|
Sign up to set email alerts
|

Potential Therapeutic Strategy in Chronic Obstructive Pulmonary Disease Using Pioglitazone-Augmented Wharton's Jelly-Derived Mesenchymal Stem Cells

Abstract: BackgroundA recent study reported that mesenchymal stem cells possess potential cellular therapeutic properties for treating patients with chronic obstructive pulmonary disease, which is characterized by emphysema. We examined the potential therapeutic effect of Wharton's Jelly-derived mesenchymal stem cells (WJMSCs), following pretreatment with pioglitazone, in lung regeneration mouse emphysema models.MethodsWe used two mouse emphysema models, an elastase-induced model and a cigarette smoke-induced model. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…For example, MSCs were reported to enhance the therapeutic capabilities of tendon repair when pretreated with pioglitazone (196). Other studies using pioglitazone as the priming agent also found similar results, where pretreated MSCs had greater therapeutic effects on lung regeneration in an emphysema mouse model (197,198). Pioglitazone has been administered indirectly to breast cancer cells via stem-and-cancer cell interaction (199).…”
Section: Potential Strategy In Utilizing Mscs For Cancer Therapymentioning
confidence: 90%
“…For example, MSCs were reported to enhance the therapeutic capabilities of tendon repair when pretreated with pioglitazone (196). Other studies using pioglitazone as the priming agent also found similar results, where pretreated MSCs had greater therapeutic effects on lung regeneration in an emphysema mouse model (197,198). Pioglitazone has been administered indirectly to breast cancer cells via stem-and-cancer cell interaction (199).…”
Section: Potential Strategy In Utilizing Mscs For Cancer Therapymentioning
confidence: 90%
“…23 Pioglitazone can reduce sepsis-induced lung injury by reducing inflammation 19 and potentiate the repair of lung injury by mesenchymal stem cells. 20,21 Therefore, the mechanisms of a lower risk of COPD might be related to an upregulation and activation of PPARγ and the subsequent anti-inflammatory effects and injury repair capability of pioglitazone.…”
Section: Discussionmentioning
confidence: 99%
“…Pioglitazone effectively prevents sepsis-induced lung injury in mice by reducing inflammation. 19 In emphysema mouse models, pioglitazone-pretreated adipose-derived mesenchymal stem cells 20 and Wharton's Jelly-derived mesenchymal stem cells 21 were more potent in the repair of lung injury. In in vitro and in vivo models of COPD, TZDs, including rosiglitazone, pioglitazone and ciglitazone, attenuated pulmonary inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…BMSCs can quickly migrate from the BM into the peripheral circulation, mobilize to injury sites and differentiate into EPCs that further differentiate into VECs to repair the injury ( 21 ). MSCs have potential therapeutic roles in the treatment of obstructive sleep apnea-hypopnea syndrome (OSAHS) ( 22 ) and COPD ( 23 , 24 ). Previous studies have revealed that BMSCs can differentiate into alveolar epithelial cells in animals with lung injury and can repair pathological tissue ( 25 , 26 ).…”
Section: Introductionmentioning
confidence: 99%